QM/MM analysis of effect of divalent metal ions on OPRT action. (June 2018) - Subrahmanyeswara Rao, N.N.; Deshpande, Parag A.
Graphical abstract: Highlights: QM/MM framework applied to describe the divalent role of metal ions in OPRT action. Mg 2+ complexation with PRPP found necessary for substrate binding. Ca 2+, Mn 2+, Co 2+ and Zn 2+ ions also tested. Energetics developed for substrate binding with all divalent metal ions. A series of experimental observations on activating/inhibitory effects explained. Abstract: The role of Mg 2+ cofactor in orotate phosphoribosyltransferase (OPRT) catalyzed synthesis of orotidine monophosphate (OMP) from phosphoribosyl pyrophosphate (PRPP) and orotate (OA) in substrate binding and the influence of the identity of the divalent metal ion on the reaction mechanism were addressed in this study using quantum mechanics/molecular mechanics framework. Energetics of migration and binding of different substrate complexes in the active site cavity was established. A quantitative analysis of various processes indicated the reaction pathway to consist of complexation of Mg 2+ with PRPP, migration of Mg 2+ -PRPP and OA towards the active site, binding of OA to OPRT, and binding of Mg 2+ -PRPP complex to OA-OPRT complex. The mechanism of the reaction was unaltered by the change in the identity of divalent metal ion. Experimentally reported inhibiting character of Co 2+ was explained on the basis of large Co 2+ -PRPP binding and migration energies. Mg 2+, Ca 2+, Mn 2+, Co 2+ and Zn 2+ ions were screened computationally to assess their inhibiting/activating characteristics. Trends obtained by our computational investigations were in correspondence with experimentally reported trends.